URGENSI MITIGASI RISIKO DALAM PEMBINAAN AKHLAK DI SMPN 16 JAKARTA SELATAN - Daffa Akmal, Mochamad; Kosasih Ali Abu Bakar; Hasan Basri Rahman; Gofur Ahmad (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze risk mitigation caused by social change, social media influence, and technological development in moral development at public secondary schools. Social change and the rapid advancement of digital technology have significantly affected students’ character formation and daily behavior. Uncontrolled use of social media and technological development may create various educational risks, such as declining discipline, lack of respect toward teachers, weak self- control, and changes in students’ behavior. Therefore, schools need to implement risk mitigation strategies through strategic planning in moral development in order to maintain a conducive educational environment and strengthen students’ character.This study employed a qualitative approach using a case study method conducted at SMPN 16 South Jakarta. Data collection techniques included observation, interviews, and documentation. The research informants consisted of Mrs. Rakhmah Hasanah as an Islamic Education teacher, Mrs. Titin Ayunah as a Guidance and Counseling teacher, Mr. Nurul Anwar as a subject teacher, homeroom teachers, and several students of SMPN 16 South Jakarta. Data analysis techniques included data reduction, data presentation, and conclusion drawing. The findings revealed that risk mitigation was implemented through moral development programs, strengthening school culture, social media education, supervision of technology use, and religious activities such as congregational prayers, Qur’an recitation, the 5S culture, Islamic mentoring, and Islamic holiday activities. These programs had a positive impact on improving discipline, strengthening students’ character, and creating a more religious and conducive school environment.